El uso de los recursos didácticos por parte de los docentes de lengua y literatura y su influencia en el desarrollo de la macrodestreza de escuchar en los estudiantes de 10 º año de educación general básica del instituto Nuestra Señora del Rosario del cantón Catamayo provincia de Loja durante el año lectivo 2012-2013 - Ontaneda Herrera, Jasmina Elizabeth (2015)
This research is based on determining if teachers of Language and Literature correctly apply the use of teaching resources for development macrodestreza heard in 10th- year Basic Education Institute "Our Lady of Rosario", the Canton Catamayo, Loja Province. For which he worked with General objective: To demonstrate whether teachers of Language and Literature correctly apply the use of teaching resources for development macrodestreza heard in 10th- year of Basic General Education Institute "Our Señora del Rosario", the Canton Catamayo, Loja Province. The work has been done carefully , using inductive, deductive , analytical, synthetic and descriptive methods , which allowed clarify the actual situation of the events in the classroom in the area of Language and Literature, and likewise; techniques like; The survey , which allowed through a questionnaire according to the topic under study, demonstrate the veracity of the previously proposed hypotheses . Field research was conducted in a total of 4 teachers and 74 students in grade 10 Basic General Education, the "Nuestra Señora del Rosario "Institute, Canton Catamayo. In conclusion it can be mentioned that teachers of the Institute "Nuestra Señora del Rosario " if they use in their language arts classes appropriate educational resources for improving listening skills .